School Managers Perceptions towards Energy Efficiency and Renewable Energy Sources - Dimitrios Drosos; Grigorios L. Kyriakopoulos; Stamatios Ntanos; Androniki Parissi (International Journal of Renewable Energy Development, 2021)
Global economic growth is accompanied by increased energy demand, thus conventional fuels such as coal, oil and gas, which are the primary energy sources, are gradually being depleted. At the same time, the combustion of conventional fuel for energy production causes serious adverse effects on the environment and contributes to climate change due to the emitted greenhouse gases. For the above reasons, most of the developed and developing countries especially during the last decades, have introduced various incentives for the greater penetration of renewable energy sources (RES) in all sectors of the economy. Concerning the building sector, several measures have been adopted, including the promotion of energy efficiency and energy saving. A significant proportion of the building stock are the school buildings where students and teachers spend a significant proportion of their daily time. Teachers' attitudes and views, especially the school unit managers concerning the use of RES in schools, are important in the effort to rationalize and control energy use. This study was conducted through a structured questionnaire applied to a sample of 510 school managers in Greece's primary and secondary education. The school unit managerial role for the case of Greek schools is performed by the school principal who has both administrative and educational duties.  Statistical analysis included the application of Friedman's test and hypothesis test on questions concerning school manager environmental perceptions and energy-saving habits. According to the results, Greek school managers have a high degree of environmental sensitivity, since 97.6 % agreed or strongly agreed that the main concern should focus on energy saving. Furthermore, 71% of the respondent reported to have good knowledge on solar energy, followed by 64% on wind energy while only 34% are knowledgeable on biomass. Almost all the respondents (99%) agreed that it is important to provide more RES-orientated education through the taught curricula. Concerning energy saving behaviour, around 90% reported that they switch off the lights when leaving the classroom and they close the windows when the air-condition is operating. Hypothesis tests revealed a relationship between the school managers' ecological beliefs, the energy saving habits in the school environment, and the recognition of the importance of environmental education. Conclusions highlighted the need to intensify environmental education programs in the school environment concerning RES in schools. This will lead to a higher level of environmental awareness of both teachers and students and therefore to a more dynamic behaviour towards the effort to “greenify” the school environment.